2007
DOI: 10.1097/01.wnf.0000240947.51994.96
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Treatment With Risperidone in Clozapine-Resistant Schizophrenia

Abstract: Despite the contradictory nature of the published data, our results are in support of other work reporting that treatment with a combination of clozapine and risperidone, apart from being well tolerated, may constitute an effective alternative in this type of patient. Nevertheless, there is a need for further, controlled studies, with larger samples, with a view to drawing definitive conclusions and making specific recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Consequently, a case report and review demonstrated that the combination of clozapine and risperidone was well tolerated and effective in treating patients with clozapine-resistant schizophrenia. 46 Psychiatrists may have added clozapine to treat a portion of patients who did not respond well to risperidone in the present study.…”
Section: Dovepressmentioning
confidence: 98%
“…Consequently, a case report and review demonstrated that the combination of clozapine and risperidone was well tolerated and effective in treating patients with clozapine-resistant schizophrenia. 46 Psychiatrists may have added clozapine to treat a portion of patients who did not respond well to risperidone in the present study.…”
Section: Dovepressmentioning
confidence: 98%
“…It involves deterioration in social adjustment, reduction in the capacity to access rehabilitation programs, and high healthcare costs. 36 Even with overall treatment today, many patients experience variable and fluctuating remission of positive and negative symptoms. In spite of a reduced number of chronic inpatients, this hampers adaptation to the demands of daily life: studies, work, family, partner, social relations, etc.…”
Section: From Drug Resistance To Lack Of Sufficient Responsementioning
confidence: 99%
“…However, a considerable number of patients are unresponsive to clozapine or only partially respond (Mauri et al 2003): long-term studies show that 47-63% of schizophrenic patients treated with clozapine fail to respond after 12 years of treatment (Lerma-Carrillo et al 2007). …”
Section: Introductionmentioning
confidence: 97%